The State-of-the-Art of sustainable urban mobility plans in Europe. - (:unkn) unknown (My University, 2011)
The report is intended to serve as a reference and guidance document for urban mobility professionals. Different approaches to sustainable urban mobility planning exist throughout Europe. The report describes the situation regarding Sustainable Urban Mobility Plans, including current levels of awareness as well as training needs, in more than thirty European countries. Furthermore, it proposes a common Europe-wide definition and sets out the essential requirements for the preparation of a good quality Sustainable Urban Mobility Plan (SUMP).
Keywords: Individualverkehr; Fahrradverkehr; Verkehrsplanung; Stadtverkehr; Radverkehrsförderung; Nachhaltige Mobilität; Statusbericht